Phase diagram prediction and particle characterisation of Sn-Ag nano alloy for Low Melting Point Lead-Free Solders - Sopousek, Jiri; Vrestal, Jan; Zemanova, Adela; Bursik, Jiri (Journal of Mining and Metallurgy, Section B: Metallurgy, 2012)
SnAg nanoparticles (SnAg NPs) were prepared by wet synthesis. The chemical composition of the SnAg NPs was obtained by inductively coupled plasma - mass spectrometry. The prepared fine powder samples were characterized by electron microscopic technique (SEM) and thermal analysis (DSC). The nanoparticles with different size were obtained. The size dependent melting point depression (MPD) of the SnAg NPs was determined experimentally. The size dependent phase diagram of the SnAg alloy was also calculated using CALPHAD method, which has been extended to describe the surface energy of SnAg nanoparticles. The same approach was used for SnAg eutectic MPD calculations. The own experimental and theoretical results were compared with the data of the other authors. The satisfactory agreement was found.